Difference as Affirmation. The Restoring of Motherhood in Western Civilization (KULT_online, 2019)
The Symbolic Order of the Mother by the Italian philosopher and feminist Luisa Muraro is the first work translated into English (2018) from a brilliant and original body of works. Influenced by the politics of women of second-wave feminism in Italy, this book (1991) represents a continuation of the sexual difference thought elaborated during the 1970s and 1980s. The aim is to show how to correct the cancellation of the maternal order by the patriarchal disorder in Western civilization. Muraro´s view of authoritative motherhood is both literal and symbolical. The maternal order represents the presence of our mother in reference to the body of women but is equally the gift of the mother tongue that introduce humanity to culture. Its denial is a form of nihilism that affects the political freedom of men and women. The maternal order needs to be brought back by a return to loving mothers as in the first years of life when they still had authority and our complete admiration.